Spectrophotometric Determination of Propoxur and Carbosulfan with 2,4,6-Trichloroaniline as the Coupling Agent - Harikrishna, V.; Prasad, B.; Naidu, N.V.S. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method is described for the determination of propoxur (O-isopropoxy phenyl, methyl carbamate) and carbosulfan (2,3-dihydro-2,2-dimethylbenzofuran-7 -yl (dibutylaminothio) methyl carbamate) by the diazotization-coupling reaction using 2,4,6-trichloroaniline as the coupling agent. The phenols of the insecticides are generated by alkaline hydrolysis. The absorption maximum of orange coloured species were 443 nm and 440 nm. The coloured species obey Beer's law in the concentration range 0-10 ppm.